Avaliação da efetividade da farinha da casca do maracujá sobre as alterações metabólicas secundárias à terapia antirretroviral em pacientes portadores de síndrome Lipodistrófica - MARQUES, Simone do Socorro Fernandes (Universidade Federal do Pará, 2013)
Anatomical and metabolic changes are common in individuals with HIV who use high-Retroviral Therapy (HAART). We conducted a clinical trial to evaluate the effectiveness of using flour of passion fruit peel (FCM) associated with the Dietary Guideline on the metabolic changes secondary to HAART in patients with lipodystrophy in lipodystrophy clinic of the Hospital Universitário João de Barros Barreto. We evaluated 36 adult patients of both sexes, people with HIV with lipodystrophy syndrome in use of HAART. These individuals were divided into two groups (n = 18 each), group 1 received 30 grams daily FCM for 90 days associated with dietotherapeutic counseling, group 2 received only dietotherapeutic counseling. The metabolic changes were analyzed before and after intervention. The results were analyzed by BioEstat 5.0 and Diet Pro and significance level p <0.05. There was greater prevalence of males, age 40-49 years, singles and family income 1-3 times the minimum wage. The majority had 10-15 years time of HIV diagnosis and the same time the use of HAART. The scheme was first prescribed HAART 1 or 2 NRTIs + 2 IP. Lipoatrophy syndrome was more prevalent and the metabolic syndrome was detected in 19.4% of the sample. Most patients presented diagnostic nutritional Eutrophic. There was no significant difference between the two groups mentioned in any of these variables, demonstrating the homogeneity of the groups. The use of FCM was effective in reducing plasma levels of total cholesterol after 30 days of use, without, however, changing its classification, there was improvement in the plasma levels of LDL - c after the use of FCM for 90 days and improvement category (increased LDL - c rating - great) there was an increase in HDL - c after 90 days of consumption of FCM without improvement in the classification of lipoproteins, there was a decrease of plasma levels of triglycerides after 30 days of FCM and improvement category. There were no changes in blood glucose after the use of FCM. Individuals who used the FCM showed a lower risk of developing coronary artery disease after 90 days of use. There was no difference between the two groups regarding the consumption of the main components of food. The use of 30 grams of FCM for 90 days associated with the Dietary Guideline is effective in improving plasma levels of total cholesterol, LDL - c, HDL – c, Triglycerides without interfering with blood glucose values.